(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Objective: To compare clinical and structural outcomes of combination therapy (anti-VEGF + PDT) versus anti-VEGF monotherapy in patients with pachychoroid neovasculopathy (PNV) during 12-month follow-up. Materials and Methods: The study included 64 patients (74 eyes) with PNV. Examinations were performed prior to treatment and at designated intervals: 1, 3, 6, and 12 months from the beginning of therapy. Patients were divided into two groups: the main group (40 eyes) and the control group (34 eyes). The main group included 34 patients (40 eyes), with baseline central retinal thickness (CRT) of 410.26 ± 113.48 µm and central choroidal thickness (CCT) of 485.89 ± 102.65 µm. The control group included 30 patients (34 eyes), with CRT of 405.89 ± 102.65 µm and CCT of 483.46 ± 102.54 µm. Patients in the main group received the following combined regimen: one intravitreal injection of 6 mg brolucizumab followed by one session of PDT with chlorin e6–based photosensitizer. Thus, during the entire observation period, patients in this group received one Anti-VEGF injection and one PDT session. PDT and brolucizumab injections were performed according to standard protocols. Subsequent treatment cycles were performed in following regimen: the interval between PDT procedures was at least 3 months, while the average interval between brolucizumab injections was approximately 1.5 months. Patients in the control group received three loading injections of 6 mg brolucizumab at 4-week intervals. Results: In the main group, BCVA increased moderately from 0.28 ± 0.14 at baseline to 0.38 ± 0.23 at the 12-month follow-up, whereas in the control group it remained relatively stable, measuring 0.31 ± 0.26 at month 1 and 0.35 ± 0.24 at month 12. Improvement in functional outcomes was accompanied by anatomical improvements: a reduction in central retinal thickness (CRT) from 410.26±113.48 μm to 262.46±146.40 μm at the 12-month follow-up, confirmed by the resorption of subretinal fluid (SRF) and a decrease in retinal pigment epithelium (RPE) detachments. A significant reduction in central choroidal thickness (CCT) was noted—from 485.89±102.65 μm to 413,21±96,23 μm after 1 month, 413,91±92,25 μm after 3 months, 414,21± 106,23 μm after 6 months, 415,30±108,64 μm by the end of the monitoring period. In the control group, improvement in BCVA was less pronounced (0.31±0.26 before treatment and 0.35±0.24 at 12 months). Changes in morphological parameters occurred early: CRT was reduced by the first month of observation (from 405.89±102.65 μm before therapy to 267,35± 43,65 μm after 1 month, 266,45± 93,65 μm after 3 months, 266,45± 93,65 μm after 6 months, followed by a slight raise up to 268,4±43,5μm by the 12-month mark. Therefore, CCT remained stable throughout the treatment period, maintaining a value comparable to baseline (483.46 ± 102.54 μm). A significant reduction in central retinal thickness and central choroidal thickness, as well as improvement in BCVA, was observed in the combination therapy group over the 6- and 12-month follow-up periods compared to the brolucizumab monotherapy group. These effects were associated with the resorption of subretinal fluid as a result of neovascular membrane occlusion. Conclusion: The inclusion of photodynamic therapy (PDT) with a chlorin e6-based photosensitizer in the treatment regimen for pachychoroid neovasculopathy (PNV) leads to the restoration of anatomical and functional parameters and reduces the recurrence of the disease in patients with PNV.